Genomes and Evolution of Charophytes, Bryophytes, Lycophytes and Ferns - Rensing, Stefan A. (Advances in botanical research, 2016)
Genome sequences of nonvertebrate genomes have greatly informed our understanding of animal evolution. In similar fashion, the sequencing of the genomes of the moss Physcomitrella patens and of the lycophyte Selaginella moellendorffii have helped to unriddle plant evolution by means of comparative genomics and evolutionary develomental (evo-devo) studies. However, many extant land plant lineages of non-seed plants still did not have a representative with a sequenced genome until recently, or are work in progress. The focus of this book is on these so far neglected lineages, namely charophyte algae that are the sister group of the land plants, the paraphyletic bryophytes (hornworts, mosses and liverworts), as well as the lycophytes (club mosses) and ferns.